High commitment HRM and burnout of frontline food service employees: a moderated mediation model. Issue 6 (29th April 2021) - Teo, Stephen T.T.; Nguyen, Diep; Shafaei, Azadeh; Bentley, Tim
Abstract : Purpose: Drawing from the Job Demands-Resources (JD-R) framework and Conservation of Resources (COR) theory, the authors' study examines the impact of high commitment HR management (HCHRM) practices and psychological capital (PsyCap) on job autonomy and job demands in predicting burnout in frontline food service employees. Design/methodology/approach: A moderated mediation model was developed and tested on 257 Australian workers employed in the food service industry. Hypotheses were tested using structural equation modeling. Findings: There was support for the mediation effect of HCHRM on burnout, via two sequential mediators: job autonomy and job demands. PsyCap was found to buffer (moderation) the effect of job demands on burnout. Frontline employees also perceived HCHRM to be a "negative signal" that was implemented for the good of management. Research limitations/implications: The authors are aware of the potential of common method variance due to the cross-sectional research design. Future research should adopt a longitudinal research design or collect data from several sources of informants. As the authors did not find support for the optimistic perspective hypothesis, despite its theoretical and empirical relevance under JD-R and COR perspectives, they call for further research exploring the link between HRM, job design and psychological conditions in promoting employee wellbeing. Practical implications: Burnout is one of the most common and critical health issues faced by frontline food service employees. Food service organizations have to strategize their management practices to reduce employees' experience with burnout by implementing high commitment enhancing HR practices and developing employees' PsyCap. Originality/value: This study provided a better understanding of how (macro) HCHRM practices as an organizational resource reduce burnout of frontline food service employees via two (micro) mediators: job autonomy and job demands. PsyCap is an important personal resource that lessens burnout, consistent with the COR theory. These findings contribute to the literature on strategic HRM and its relationship to employee wellbeing.